Action naming deficits in Parkinson’s disease: the role of semantic complexity - Anyfantis, Emmanouil; Messinis, Lambros; Kambanaros, Maria; Konitsiotis, Spyridon (My University, 2023)
Background: Previous studies have suggested that individuals with Parkinson’s disease (PD) have difficulty retrieving verbs and nouns. Among the factors that have been proposed to contribute to this verb retrieval difficulty is the semantic properties of the verbs. Aims: The aim of this study was to investigate the verb and noun naming abilities in Greek speaking individuals with PD. Furthermore, the effect of semantic complexity on verb retrieval ability was explored. Specifically, two verb categories were investigated mainly, instrumental verbs as semantically heavy and non-instrumental verbs that are considered semantically light verbs. Methods and Procedures: Participants were 24 non-demented individuals with PD matched for age and education with 15 healthy control participants. Word retrieval abilities for nouns and verbs were evaluated using the Greek Object and Action Test (GOAT), a picture-based assessment of single word retrieval. Outcomes and Results: The results revealed that participants with PD performed significantly worse on naming verbs and nouns compared to healthy controls. Specifically, the PD group had a greater difficulty in retrieving verbs compared to nouns. In addition, a positive effect of instrumentality on verb retrieval abilities was observed. Conclusion: The results of this study suggest that semantic complexity may play a critical role in verb retrieval abilities in PD. Furthermore, verbs related to upper limb movement with the inclusion of instrumental verbs may have a facilitatory effect on lexical retrieval. This finding emphasizes the need for the inclusion of the evaluation of different verb categories for naming during the initial clinical assessment of cognitive-linguistic abilities of patients with PD.
Keywords: executive dysfunction; instrumentality; Parkinson’s disease; picture naming task; semantic complexity; verb retrieval deficits